Estimated Placental Volume and Gestational Age - Isakov, Kimberly M. M.; Emerson, John W.; Campbell, Katherine H.; Galerneau, France; Anders, Amber M.; Lee, Yoonjoo K.; Subramanyam, Pritha; Roberts, Andrea E.; Kliman, Harvey J. (American Journal of Perinatology, 2018)
Objective The objective of this study was to validate estimated placental volume (EPV) across a range of gestational ages (GAs).Study Design Three hundred sixty-six patients from 2009 to 2011 received ultrasound scans between 11 + 0 and 38 + 6 weeks GA to assess EPV. An EPV versus GA best fit curve was generated and compared with published normative curves of EPV versus GA in a different population. A subanalysis was performed to explore the relationship between EPV and birth weight (BW).Results Analysis of EPV versus GA revealed a parabolic curve with the following best fit equation: EPV = (0.372 GA − 0.00364 GA2)3. EPV was weakly correlated with BW, and patients with an EPV in the bottom 50th percentile had 2.42 times the odds of having a newborn with a BW in the bottom 50th percentile (95% confidence interval: 1.27–4.68). Microscopic evaluation of two placentas corresponding to the smallest EPV outliers revealed significant placental pathology.Conclusion Placental volume increases throughout gestation and follows a predictable parabolic curve, in agreement with the existing literature. Further validation is required, but EPV may have the potential for clinical utility as a screening tool in a variety of settings.
Keywords: placenta; volume; ultrasound; birth weight